Identification of pre-clinical cardiovascular imaging phenotypes related to blood pressure in young adults - Alsharqi, M (2021)
Hypertension prevalence in young adults is rising and is associated with an increased risk of stroke and cardiovascular disease in later life. However, hypertension management guidelines for patients below the age of 40 years remain conservative as their absolute risk of imminent vascular events is low. Additionally, due to the relatively short duration of exposure to hypertension, traditional measures of target organ damage such as left ventricular hypertrophy are often normal. In this thesis, I sought to identify pre-clinical cardiovascular phenotypes associated with blood pressure elevation in young adults, which might be of value for monitoring disease progression in young people.